The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12903-020-01239-8
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study of the effect of 5-ALA-mediated photodynamic therapy on oral squamous cell carcinoma

Abstract: Background The primary aim of this study was to observe the effect of 5-ALA-mediated photodynamic therapy on oral squamous cell carcinoma in vitro. Methods SCC25 cells were divided into the observation group and the blank control group. Different concentrations of 5-ALA and SCC25 cells were co-incubated for different times, and the concentration of protoporphyrin IX was detected by flow cytometry. SCC25 cells were divided into the 5-ALA group (100 mg/L), the laser irradiation group alone, the 5-ALA plus lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
(15 reference statements)
0
18
0
Order By: Relevance
“…Moreover, the parameters we mention in Table 1 (cell name, duration of incubation, irradiation wavelength, fluence, and duration between irradiation and viability assays) should be clearly mentioned in Section 2 because all of these parameters possibly affect the sensitivity of cells to 5-ALA PDT and the results of cell viability assays. Comparisons of the duration of 5-ALA incubation [ 35 , 68 , 103 ], irradiation wavelength [ 104 , 105 ], and fluence [ 30 , 31 ] showed that each parameter strongly affected cell viability. In addition, the duration between irradiation and viability assays can also affect the results because cell proliferation after light irradiation can be influenced by the number of viable cells with a sigmoid shape.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…Moreover, the parameters we mention in Table 1 (cell name, duration of incubation, irradiation wavelength, fluence, and duration between irradiation and viability assays) should be clearly mentioned in Section 2 because all of these parameters possibly affect the sensitivity of cells to 5-ALA PDT and the results of cell viability assays. Comparisons of the duration of 5-ALA incubation [ 35 , 68 , 103 ], irradiation wavelength [ 104 , 105 ], and fluence [ 30 , 31 ] showed that each parameter strongly affected cell viability. In addition, the duration between irradiation and viability assays can also affect the results because cell proliferation after light irradiation can be influenced by the number of viable cells with a sigmoid shape.…”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…The following data were extracted and tabulated: cell line, PS and its concentration type of light source, wavelength, energy density (J/cm 2 ), type of evaluation, and main outcomes (Table S1, Supplementary file 1). 9,23,…”
Section: Data Extractionmentioning
confidence: 99%
“…While selectively destroying malignant cells and tissues, it is not affected by drug resistance and does not have the systemic side effects of other routine treatment methods like chemotherapy. 9,10 Cancer tissue destruction by PDT can be a result of direct cytotoxicity, vascular injury or a local inflammatory response that subsequently leads to a systemic anti-tumor immunological effect. [11][12][13] The concept of PDT was initially introduced by Oscar Raab in 1898, who found that paramecia incubated with a fluorescent dye were killed after being exposed to light.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the effectiveness of the former, it cannot be applied in all cases due to adverse malignancy’s localization and potential patient’s co-morbidities [ 2 ]. Moreover, radiotherapy and chemotherapy can not only be toxic and lead to side effects but also might be ineffective in cells with developed resistance [ 4 ], whereas immunotherapy currently seems too complex for general use [ 5 ]. Therefore, further development of more efficient therapeutic strategies is still required.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, presently, PDT is not applicable in the treatment of metastatic cells [ 10 ]. The most common PS evoke a low therapeutic effect against highly pigmented melanoma cells [ 5 ], and the method itself can be burdened with pain, especially in combination with commonly used 5-aminolevulinic acid (5-ALA) [ 4 ]. For all those reasons, PDT enhancement is currently extensively investigated, especially with novel, high-efficient, and less toxic photosensitizers.…”
Section: Introductionmentioning
confidence: 99%